Romantika Perkawinan Beda Agama di Indonesia - Gusti Muhamad Shadiq; Ahmadi Hasan; Masyithah Umar (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
Abstract This paper discusses marriage in Indonesia, focusing on interfaith marriages. While the Marriage Law does not explicitly regulate interfaith marriages, the Civil Registration Law allows for them to be registered with a court order. However, the issuance of SEMA Number 2 of 2023 prohibits courts in Indonesia from granting applications for interfaith marriages. The paper also acknowledges the diversity of religions in Indonesia and emphasizes that every Indonesian citizen has the right to enter into marriage, regardless of their religion. The Marriage Law states that marriage is the bond between a man and a woman with the aim of forming a happy and lasting family based on God Almighty. The validity of marriage is based on the religion/belief of the individuals involved. If a person's religion prohibits them from marrying someone of a different religion, the marriage would be considered invalid. Overall, the paper highlights the complexities and challenges surrounding interfaith marriages in Indonesia. Keywords: Marriage, different, religion, Indonesia Abstrak: Penelitian ini membahas pernikahan di Indonesia, dengan fokus pada pernikahan beda agama. Meskipun UU Perkawinan tidak secara eksplisit mengatur pernikahan beda agama, UU Adminduk mengizinkan pernikahan beda agama untuk didaftarkan dengan penetapan pengadilan. Namun, penerbitan SEMA Nomor 2 Tahun 2023 melarang pengadilan di Indonesia untuk mengabulkan permohonan pernikahan beda agama. SEMA tersebut juga mengakui keragaman agama di Indonesia dan menekankan bahwa setiap warga negara Indonesia memiliki hak untuk melangsungkan pernikahan, terlepas dari agama mereka. Undang-Undang Perkawinan menyatakan bahwa perkawinan adalah ikatan lahir batin antara seorang pria dan seorang wanita dengan tujuan membentuk keluarga yang bahagia dan kekal berdasarkan Ketuhanan Yang Maha Esa. Keabsahan pernikahan didasarkan pada agama/kepercayaan masing-masing individu yang terlibat. Jika agama seseorang melarang mereka untuk menikah dengan orang yang berbeda agama, maka pernikahan tersebut dianggap tidak sah. Secara keseluruhan, penelitian ini menyoroti kompleksitas dan tantangan seputar pernikahan beda agama di Indonesia. Kata Kunci: Perkawinan, beda, agama, indonesia